Pilot study of a comprehensive multidisciplinary inpatient-based approach to smoking cessation in patients with vascular disease - Tanner Kim, MD; Anand Brahmandam, MBBS; Dana Alameddine, MD; Rachel Forman, MD; Amin Hardik, MD; Lisa Fucito, PhD; Carlos Mena-Hurtado, MD; Raul Guzman, MD; Cassius Iyad Ochoa Chaar, MD, MS, MPH (JVS-Vascular Insights)
Objective: Smoking cessation remains a significant challenge in the care of patients with vascular disease. This pilot study aims to evaluate the efficacy of a multidisciplinary inpatient smoking cessation intervention that leverages surgery as a teachable moment and the postoperative inpatient recovery period to initiate smoking cessation counseling and pharmacotherapy. Methods: Adult smokers with occlusive or aneurysmal arterial disease admitted after vascular surgery in a tertiary care center were enrolled. Patients received brief counselling sessions regarding smoking cessation from specialties including vascular surgery, cardiology, neurology, and the smoking cessation program during the hospitalization using the gain-frame approach. Subjects completed surveys related to smoking habits and mental health, including the Fagerstrom test for nicotine dependence and Patient-Reported Outcomes Measurement Information System questionnaire, respectively. Patients were provided free nicotine replacement therapy for 4 weeks. Any additional medication deemed necessary for quitting was prescribed upon discharge. Patients were given appointments for a smoking cessation program visit and routine provider follow-up was scheduled. The primary end points were smoking cessation rates at 3 months and 1 year. Results: A total of 48 patients were enrolled. The mean number of cigarettes consumed before enrollment was 17 ± 9 per day over a mean period of 40 ± 11 years. All patients had previously attempted to quit smoking and 97% had received advice from their surgeons or interventionalists to quit smoking in the prior year. Most patients (94%) had tried to stop smoking before and 50% had more than three attempts at smoking cessation before enrollment. The mean quitting period was 9 months (range, 4-20 months) before relapse. Stress was the most common reason for relapse and continued smoking in 50% of patients. A minority of patients knew that smoking was taking years off their life (42%), made them worry about developing heart disease (34%), and reduced their quality of life (31%). At 1 year, the smoking cessation rate was 45% (n = 19/42) with 59% (n = 25/42) reduced smoking quantity. The carbon monoxide breath test was not conducted owing to the coronavirus disease 2019 pandemic. Conclusions: This pilot study demonstrates that an inpatient, multidisciplinary approach to smoking cessation is effective with a durable impact up to 1 year. Inpatient strategies leveraging multidisciplinary teams and teachable moments should be incorporated into smoking cessation programs.